LDB2 locus disruption on 4p16.1 as a risk factor for schizophrenia and bipolar disorder - Horiuchi, Yasue (Hum Genome Var, 2020)
We had previously reported the case of a male patient with schizophrenia, having de-novo balanced translocation. Here, we determined the exact breakpoints in chromosomes 4 and 13. The breakpoint within chromosome 4 was mapped to a region 32.6 kbp upstream of the LDB2 gene encoding Lim domain binding 2. Variant screening in LDB2 revealed a rare novel missense variant in patients with psychiatric disorder.